Serum Levels of S-100B after Recreational Scuba Diving - Stavrinou, L. C.; Kalamatianos, T.; Stavrinou, P.; Papasilekas, T.; Psachoulia, C.; Tzavara, C.; Stranjalis, G. (International Journal of Sports Medicine, 2011)
Recreational scuba diving is a sport of increasing popularity. Previous studies indicating subtle brain injury in asymptomatic divers imply a cumulative effect of minor neural insults in association with diving for professional and/or recreational purposes, over the long-term. This is the first study to investigate putative neural tissue burden during recreational scuba diving by measuring circulating levels of S-100B, a sensitive biomarker of brain injury. 5 male divers performed 3 consecutive dives under conservative recreational diving settings (maximum depth 15 m, duration of dive 56 min, ascend rate 1.15 m/min) with an interval of 12 h between each session. Although a small increase in serum S-100B levels after each dive was apparent, this increase did not quite reach statistical significance (p=0.057). Moreover, no abnormal S-100B values were recorded (mean baseline: 0.06 μg/L, mean post-dive: 0.086 μg/L) and no effect of the 3 consecutive dives on changes in S-100B levels was detected. These results suggest that under the experimental conditions tested, diving does not seem to have a discernible and/or cumulative impact on central nervous system integrity. The extent to which variable diving settings and practices as well as individual susceptibility factors underlie putative neural tissue burden in asymptomatic divers, remains to be established.
Keywords: scuba diving; S100b; biomarker; brain injury